2003
DOI: 10.1007/s00216-003-2197-2
|View full text |Cite
|
Sign up to set email alerts
|

Rapid determination of telmisartan in pharmaceuticals and serum by the parallel catalytic hydrogen wave method

Abstract: The polarographic characteristics of telmisartan have been investigated in 0.8 mol L(-1) NH3.H2O-NH4Cl (pH 8.9)-0.01 mol L(-1) H2O2 as supporting electrolyte. The results demonstrate that the polarographic reduction wave at ca. -1.30 V in the absence of H2O2 is a catalytic hydrogen wave, and the reduction wave enhanced by H2O2 is a so-called parallel catalytic hydrogen wave. The analytical sensitivity of the parallel catalytic hydrogen wave is ca. 60 times higher than that of the corresponding catalytic hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In all other electrochemical studies [19][20][21] and almost all chromatographic studies [5][6][7][8][9][10][11][12], relatively high concentration of TS was studied and limit of detection value was found to be higher than current study. Both LOD and LOQ values confirmed the sensitivity of the proposed methods.…”
Section: Methods Validationmentioning
confidence: 58%
See 1 more Smart Citation
“…In all other electrochemical studies [19][20][21] and almost all chromatographic studies [5][6][7][8][9][10][11][12], relatively high concentration of TS was studied and limit of detection value was found to be higher than current study. Both LOD and LOQ values confirmed the sensitivity of the proposed methods.…”
Section: Methods Validationmentioning
confidence: 58%
“…All these reported methods require highly sophisticated instrumentation even they are sufficiently sensitive. TS is an electroactive molecule on different electrodes therefore there are three studies dealing with electrochemical determination of TS based on mercury [19,20] and carbon paste [21] electrodes. Reviewing the literature revealed that, up to the present time, there is no square-wave cathodic stripping voltammetric method using mercury electrode to assay of TS in pharmaceutical formulation and biological samples.…”
Section: Introductionmentioning
confidence: 99%
“…The advance in experimental electrochemical techniques in the field of analysis of drugs is due to their simplicity, low cost, and relatively short analysis time as compared with the other techniques. However, since most drugs are less active electrochemically, little attention has been paid so far to the use of electrochemical detection methods [40][41][42][43].…”
Section: Electrochemical Methods Of Analysismentioning
confidence: 99%
“…Xu et al [42] investigated the polarographic characteristics of telmisartan in 0.8 mol/l NH 3 ÁH 2 O-NH 4 Cl (pH 8.9)-0.01 mol/l H 2 O 2 as supporting electrolyte. The calibration curve is linear in the range of 2.0 Â 10 À8 -2.0 Â 10 À6 mol/l and the detection limit is 1.0 Â 10 À8 mol/l.…”
Section: Polarographymentioning
confidence: 99%
“…Accordingly, it was deduced that the reduction wave of CAN at -1340 mV in the optimal supporting electrolyte should be the result of the reduction of the proton rather than that of the other groups; this produces a catalytic hydrogen wave. Owing to the ability of the nitrogen atom to combine with a hydrogen ion being higher than that of an oxygen atom, the nitrogen atom of CAN combines with a hydrogen ion in the benzimidazole and tetrazol groups, yielding electroactive compounds on the cathode [24,25].…”
Section: Characterization Of the Electrode Reactionmentioning
confidence: 99%